Management of Complications Associated With Gorham-Stout Disease: Case Report and Review of the Literature. (20th May 2022) - Zupelari Goncalves, Paulo; Shelgikar, Anita; Edwards, Sean; Stanley, Jeffrey; Aronovich, Sharon
This case report describes the course of a patient diagnosed with Gorham-Stout Disease and reviews known complications and treatment options for this rare condition. An emphasis is placed on potential multi-systemic complications that may occur including surgical complications, obstructive sleep apnea, post-operative airway obstruction, respiratory failure and cardiac arrest.